Receptor for advanced glycation end products: a key molecule in the genesis of chronic kidney disease vascular calcification and a potential modulator of sodium phosphate co-transporter PIT-1 expression. Issue 12 (18th February 2019) - Belmokhtar, Karim; Ortillon, Jeremy; Jaisson, Stéphane; Massy, Ziad A; Boulagnon Rombi, Camille; Doué, Manon; Maurice, Pascal; Fritz, Günter; Gillery, Philippe; Schmidt, Ann Marie; Rieu, Philippe; Touré, Fatouma
Abstract: Background: Chronic kidney disease (CKD) is associated with increased cardiovascular mortality, frequent vascular calcification (VC) and accumulation of uraemic toxins. Advanced glycation end products and S100 proteins interact with the receptor for advanced glycation end products (RAGE). In the present work, we aimed to investigate the role(s) of RAGE in the CKD–VC process. Methods: Apoe −/− or Apoe −/− Ager (RAGE) −/− male mice were assigned to CKD or sham-operated groups. A high-phosphate diet was given to a subgroup of Apoe −/− and Apoe −/− Ager −/− CKD mice. Primary cultures of Ager +/+ and Ager −/− vascular smooth muscle cells (VSMCs) were established and stimulated with either vehicle, inorganic phosphate (Pi) or RAGE ligands (S100A12; 20 µM). Results: After 12 weeks of CKD we observed a significant increase in RAGE ligand (AGE and S100 proteins) concentrations in the serum of CKD Apoe −/− mice. Ager messenger RNA (mRNA) levels were 4-fold higher in CKD vessels of Apoe − / − mice. CKD Apoe −/− but not CKD Apoe −/− or Ager −/− mice displayed a marked increase in the VC surface area. Similar trends were found in the high-phosphate diet condition. mRNA levels of Runx2 significantly increased in the Apoe −/− CKD group. In vitro, stimulation of Ager +/+ VSMCs with Pi or S100A12 induced mineralization and osteoblast transformation, and this was inhibited by phosphonoformic acid (Pi co-transporters inhibitor) and Ager deletion. In vivo and in vitro RAGE was necessary for regulation of the expression of Pit-1, at least in part through production of reactive oxygen species. Conclusion: RAGE, through the modulation of Pit-1 expression, is a key molecule in the genesis of VC.